التعويض الأمثل للاستطاعة الردية في شبكات التوزيع الكهربائية باستخدام النظم الخبيرة - اسبر, جورج; شعبان, فيصل; رزوق, سنان (Latakia University Journal -Engineering Sciences Series, 2019)
لقد تناولنا في هذا البحث موضوع تخفيض الضياع في شبكات التوزيع الكهربائية باستخدام المكثفات كونها الوسيلة الأنجع والأسهل من حيث التطبيق العملي لخفض الضياعات في شبكات التوزيع الكهربائية إلى حدها الأصغري. إن عملية استخدام المكثفات لتخفيض الضياعات في شبكات التوزيع الكهربائية إلى حدها الأصغري تؤول في الحالة العامة إلى عملية أمْثَلة Optimizing وبحث عن الحل الأمثل Optimum search. إذ إن الحل الأمثل لهذه المسألة يتأثر بعددٍ كبيرٍ من العوامل والقيود الفنية والاقتصادية، لذا فإن مسألة أمْثَلة استخدام المكثفات لتخفيض الضياعات في شبكات التوزيع الكهربائية، إذا ما أخذنا الطبيعة المتقطعة Discrete لمتحولاتها بالحسبان، هي من المسائل المعقدة وتحتاج إلى تقنية متطورة للبحث عن الحل الأمثل والوصول إليه بسرعة معقولة. في هذا العمل تمت الاستفادة من تقنيات الذكار الصنعي AI لحل مسألة أمْثَلة استخدام المكثفات لتخفيض الضياع في شبكات التوزيع الكهربائية و قد تم بناء نظام خبير Expert system يساعدنا في البحث عن الحل الأمثل لمسألتنا هذه والوصول إليه بسرعة وبأقل جهد ممكن. This research discusses the subject of loss reduction in electrical distribution networks by using condensers as being the easiest and most effective means in the filed of practical application for reducing losses in the electrical distribution networks to their minimal level. Using condensers for reducing losses in the electrical distribution networks to their minimal limit is attributed in general state to an optimizing operation and a research for the optimal solution. As the optimal solution of this question is affected by a great number of technical and economic factors and restrictions; therefore, the process of optimizing the use of condensers to reduce losses in electrical distribution networks, if we take the discrete nature of their transformations into consideration, is one of the complicated problems and it needs advanced technology to look for the optimal solution and to approach it at a reasonable speed. In this task we should make use of the artificial intelligence technology to solve the problem of optimizing the use of condensers for reducing losses in electrical distribution networks, and an expert system has been constructed to help us in searching for the optimal solution for this problem of ours and to approach it quickly with the least possible effort.